Culture As a Source of Learning: Integration of Merauke Local Wisdom in Deep Learning Approach - Amri, Haerul; Rapsanjani, Hafsemi; Fredy, Fredy; Yohanes, Rizki Adri; Rahim, Abdul (Journal of Authentic Research, 2025)
This study aims to analyze the integration of Merauke's local wisdom into deep learning through a literature study using a qualitative approach. Deep learning is understood as a pedagogical approach that emphasizes mindful, meaningful, and joyful learning, thereby encouraging students to construct conceptual understanding, think critically, and apply knowledge contextually. On the other hand, Merauke's local wisdom, reflected in the practices of totemism, adat sasi, yur traditions, as well as social rituals and traditional leadership systems, has ecological, social, and spiritual values that are relevant to contextual education. The results of the analysis show that integrating the two can strengthen cultural literacy, ecological awareness, and character building among students. The ecological values in sasi and yur can be used for meaningful learning, spiritual and social values such as “Izakod Bekai Izakod Kai” are relevant for mindful learning, while traditional celebrations contribute to joyful learning. However, challenges such as limited infrastructure, teacher competence, and scientific validation of local knowledge need to be overcome through training, innovative learning media, and an ethnoscience approach. This research concludes that integrating deep learning with Merauke's local wisdom has the potential to create a contextual pedagogical model that not only enriches the learning experience but also preserves cultural identity and supports sustainable education.